Impacts of the Trilemma Policies on Inflation, Growth and Volatility in Greece - Hsing, Yu (International Journal of Economics and Financial Issues, 2012)
This paper finds support for the trilemma for Greece, suggesting that there is a tradeoff among exchange rate stability, monetary independence and financial integration. The policy combination of monetary independence and financial integration has been prevalent. More exchange rate stability does not affect the inflation rate, the growth rate, inflation volatility and output volatility. More monetary independence reduces output volatility. More financial integration reduces inflation, inflation volatility and output volatility. Hence, more financial integration or monetary independence is beneficial to Greece. Keywords: Trilemma; Exchange rate stability; Monetary independence; Financial integration; Inflation; Growth; Volatility JEL Classifications: E44; E52; F31; F36